PRODUCTION FACTORS OF VANNAMEI SHRIMP ( Litopenaeus vannamei ) USING INTENSIVE AND SUPER INTENSIVE CULTIVATION TECHNIQUES IN PERCUT SEI TUAN DISTRICT, DELI SERDANG DISTRICT - Lestari, Ade Aulia; Harahap, Gustami; Ilvira, Rika Fitri (Journal of Agri Socio Economics and Business, 2024)
This research aims to determine the factors that influence Vaname Shrimp Production in Intensive cultivation and Super Intensive cultivation in Percut Sei Tuan District, Deli Serdang Regency. This research was carried out in February 2003 - March 2023 at Percut Sei Tuan District. This research was carried out purposively (purposive sampling) involving 42 vaname shrimp farmers. Data was obtained through interviews, observations and surveys using a research questionnaire. Data analysis uses multiple linear regression analysis with the Douglas Coob approach. The results of this research show that based on the results of multiple linear regression analysis using the Douglas Coob approach for intensive cultivation, it was concluded that there were no variables that had a significant effect on vaname shrimp production. Based on the results of multiple linear regression analysis tests using the Coob Douglas approach for the super intensive cultivation type, it was concluded that the variables number of fry, amount of feed and number of workers had a positive and significant effect on vaname shrimp production.